Dietary Anti-Aging Polyphenols and Potential Mechanisms - Jing Luo; Hongwei Si; Zhenquan Jia; Dongmin Liu (MDPI AG, 2021)
For years, the consumption of a diet rich in fruits and vegetables has been considered healthy, increasing longevity, and decreasing morbidities. With the assistance of basic research investigating the potential mechanisms, it has become clear that the beneficial effects of plant-based foods are mainly due to the large amount of bioactive phenolic compounds contained. Indeed, substantial dietary intervention studies in humans have supported that the supplementation of polyphenols have various health-promoting effects, especially in the elderly population. In vitro examinations on the anti-aging mechanisms of polyphenols have been widely performed, using different types of natural and synthetic phenolic compounds. The aim of this review is to critically evaluate the experimental evidence demonstrating the beneficial effects of polyphenols on aging-related diseases. We highlight the potential anti-aging mechanisms of polyphenols, including antioxidant signaling, preventing cellular senescence, targeting microRNA, influencing NO bioavailability, and promoting mitochondrial function. While the trends on utilizing polyphenols in preventing aging-related disorders are getting growing attention, we suggest the exploration of the beneficial effects of the combination of multiple polyphenols or polyphenol-rich foods, as this would be more physiologically relevant to daily life.